Anisakis sp. larvae in Plagioscion squamosissimus (Heckel, 1840) from the Curralinho municipality, Marajó Island, Pará, Brazil - Salazar de Carvalho, Simone; Araújo dos Santos Ruffeil, Luis Augusto; da Silva Pinheiro, Raul Henrique; Guerreiro Giese, Elane; Paixão Mangas, Tiago (Archives of Veterinary Science, 2025)
Abstract: Several reports from Brazil indicate the presence of fish parasitized by nematodes with zoonotic potential, notably those within the Anisakidae family. This research investigates the morphology, morphometry, and prevalence of Anisakis larvae parasitizing fish being sold in the municipality of Curralinho, in the Brazilian state of Pará. Twenty specimens of Plagioscion squamosissimus were directly collected from the Guajará River by fishers in the city of Curralinho. These fish were purchased, necropsied, and their organs were individually placed in Petri dishes containing saline solution for helminthological examination using a stereomicroscope. All the fish (100%) were found to be parasitized, and a total of 1,390 third-stage Anisakis larvae were recovered, encysted in the intestinal serosa and mesentery. The third-stage larvae were analyzed using light and scanning electron microscopy. Morphologically, the third-stage Anisakis larvae exhibited an anterior end featuring a dorsal lip and two poorly developed ventrolateral lips, a boring tooth, and an excretory pore situated below the boring tooth. Internally, they possessed a muscular esophagus, a long ventriculus, a terminal mucron, and a ventricular appendix, while an intestinal cecum was absent. The presence of these third-stage Anisakis larvae in fish sold in markets underscores their significance for public health, as these Anisakidae nematodes, especially Anisakis spp, are known to cause anisakiasis.